Dal chiasma ontologico al chiasma trascendentale. Forme di razionalità nel pensiero di Enzo Melandri - Palombini, Lorenzo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2017)
In this essay, we will examine the notion of ontological chiasm in Enzo Melandri’s work La linea e il circolo. It is a key notion with broad implication regarding the philosopher’s account of analogic rationality, which can neither be reduced to logical rationality nor separated from it, and it also provides an insightful suggestion about the formal relation between the two, which entails a special chiasmic simmetry.